2023
DOI: 10.1101/2023.04.15.537008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heritable changes of epialleles in maize can be triggered in the absence of DNA methylation

Abstract: Trans-chromosomal interactions resulting in changes in DNA methylation during hybridization have been observed in several plant species. However, very little is known about the causes or consequences of these interactions, many of which result in changes in methylation of transposable elements. Here, we compared DNA methylomes of F1 hybrids that are mutant for two small RNA biogenesis genes,Mop1(mediator of paramutation1) andLbl1(leafbladeless1) with that of their parents, wild type siblings, and backcrossed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Barber et al (2012) [ 56 ] analyzed how siRNA populations vary between two maize inbred lines (B73 and Mo17) and their hybrid in the shoot apex and the developing ear (high percentages of these siRNAs derive from retrotransposons) and found that the small RNA levels are altered in the hybrids. In the same hybrid, Liu et al (2023) [ 57 ] found that there are regions where methylation decreases after hybridization despite the production of small RNAs.…”
Section: Changes In the Epigenetic Silencing Of The Tes In Plant Inte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Barber et al (2012) [ 56 ] analyzed how siRNA populations vary between two maize inbred lines (B73 and Mo17) and their hybrid in the shoot apex and the developing ear (high percentages of these siRNAs derive from retrotransposons) and found that the small RNA levels are altered in the hybrids. In the same hybrid, Liu et al (2023) [ 57 ] found that there are regions where methylation decreases after hybridization despite the production of small RNAs.…”
Section: Changes In the Epigenetic Silencing Of The Tes In Plant Inte...mentioning
confidence: 99%
“…The DNA demethylation can activate the TE transposition [ 140 ]. The methylation status of TEs returns to near parental levels in a relatively short time (a few generations), and siRNAs play an important role in this process [ 57 ]. If the active TE content of both genomes is different, the small RNA sequences derived from one parent differ from the other, resulting in an enhanced TE activity depending on which parent contains more active TEs.…”
Section: Conclusion: Genomic Shock?mentioning
confidence: 99%